S-adenosylmethionine in rat liver cirrhosis - Cutrin, C; Menino, M; Carballo, C; Parafita, M; Perez-Becerra, E; Barrio, E (1993)
An experimental model of cirrhosis in rats, by means carbon tetrachloride (CCl4) and ethanol during two months, was used to assess the effectiveness of S-adenosylmethionine. Histological studies of the liver and examination of different biochemical parameters of hepatic function were also employed. Bilirubin and lactic acid levels decreased significantly in the group treated with S-adenosylmethionine in comparison with the CCl4 + ethanol group. Histologic liver studies showed a significant improvement relative to fatty liver, Mallory bodies, infiltrate polymorphonuclear and perivenular fibrosis. A slight decrease in cirrhosis was observed in the animals treated with S- adenosylmethionine.